Optimization of Alkaline Solution-Pure Water Combined Rehydration Process for Dried Cuttlefish and Its Texture Properties before and after Rehydrating - Junhao GU; Mingyu YIN; Xichang WANG (Shipin gongye ke-ji)
Objective: Investigation of optimized rehydration process of dried cuttlefish and its textural changes before and after rehydrating. Methods: The combination rehydration method was conducted by two-step process with alkaline solution first and pure water next, the conditions were optimized based on the rehydration ratio and protein loss. Then the textural properties of dried cuttlefish before and after rehydrating, as well as protein secondary structure, tissue morphology and other related indexes were analyzed. Results: The conditions for alkaline solution treatment of dried cuttlefish were the concentration of sodium carbonate solution 0.50%, 2.0 h of the rehydrating time, 50 ℃ of the rehydrating temperature, the ratio of material to liquid being 1:20 g/mL. On this basis, the optimal conditions for pure water treatment were 1.0 h of the rehydrating time, 50 ℃ of the rehydrating temperature, the ratio of material to liquid being 1:20 g/mL, with the rehydration ratio and protein loss of the rehydrated dried cuttlefish were 261.10%±7.10% and 16.80%±0.74% respectively. The rehydration treatment reduced the hardness, gumminess and chewiness of dried cuttlefish while the springiness increased significantly (P<0.05), and resulted in structural folding of myofibrillar protein, and enlarged the gaps between muscle fibers. Conclusion: This study clarifies the optimal rehydration parameters of dried cuttlefish and improves its textural properties to provide theoretical reference for the high-quality processing and utilization of dried cuttlefish.